2013
DOI: 10.2527/jas.2013-6304
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of digestive tract microbiome in neonatal Holstein bull calves by bacitracin methylene disalicylate treatment and scours1

Abstract: The effects of bacitracin methylene disalicylate (BMD) and scours on the fecal microbiome, animal performance, and health were studied in Holstein bull calves. Holstein bull calves (n = 150) were obtained from a single source at 12 to 24 h of age. Bull calves were randomly assigned to 1 of 2 treatments including CON (no BMD; n = 75 calves) and BMD (n = 75 calves). Starting 3 d after arrival, BMD was added into milk replacer (0.5 g/feeding; twice daily) and fed to the calves for 10 consecutive d. No differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 28 publications
1
30
1
Order By: Relevance
“…Bacitracin is one of the most extensively used AGPs to improve productivity in poultry [ 1 ]. In calves, bacitracin has been shown to alter fecal microbiota composition but did not improve animal performance [ 28 ]. Some studies have reported alterations in the gut bacterial community of broiler chickens associated with dietary supplementation with bacitracin [ 17 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacitracin is one of the most extensively used AGPs to improve productivity in poultry [ 1 ]. In calves, bacitracin has been shown to alter fecal microbiota composition but did not improve animal performance [ 28 ]. Some studies have reported alterations in the gut bacterial community of broiler chickens associated with dietary supplementation with bacitracin [ 17 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, literature on the effect of each antibiotic class on the hindgut microbiota of preweaned dairy calves is scarce. As far as we know, research on this topic has focused on a few classes: macrolides [7,24], tetracycline [7], amphenicol [7], uoroquinolones [24], and polypeptides [25]. These studies, with the exception of that by Xie et al [25], all focused on the effects of a single injection of the antibiotic, which differs from the treatment plans and route of administration (oral) in our study.…”
Section: Discussionmentioning
confidence: 87%
“…As far as we know, research on this topic has focused on a few classes: macrolides [7,24], tetracycline [7], amphenicol [7], uoroquinolones [24], and polypeptides [25]. These studies, with the exception of that by Xie et al [25], all focused on the effects of a single injection of the antibiotic, which differs from the treatment plans and route of administration (oral) in our study. Xie et al reported dysbiosis in neonatal dairy calves receiving bacitracin for 10 days in the milk replacer, characterized by an increase in the abundance of Escherichia and Enterococcus, along with a decrease in the abundance of Dorea, Collinsella, Eubacterium, Faecalibacterium, Papillibacter, Peptostreptococcus, Prevotella, and Roseburia, relative to non-exposed calves of the same age [25].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The use of antibiotics for the treatment of bovine respiratory disease and umbilical infection is a common practice among bovine practitioners (Shearer, 1986;Apley, 2015); however, the treatment of calf diarrhea with antimicrobials remains a controversial topic among veterinarians. The risk of bacteremia in diarrheic calves supports the use of antimicrobials in some cases (Fecteau et al, 1997); in contrast, the potential for causing disturbances on the intestinal microflora and increasing the risk of bacterial resistance discourages the use of antimicrobials in the treatment of calf diarrhea in other cases (Xie et al, 2013). In the present study, local and systemic protection provided by immunoglobulins and immunomodulatory molecules from the colostrum powder might have reduced the incidence of infection and therefore the need of antibiotic therapy in supplemented calves.…”
Section: Discussionmentioning
confidence: 99%